PROTEKSI KATODIK DENGAN ANODA TUMBAL SEBAGAI PENGENDALIAN KOROSI BAJA DALAM LINGKUNGAN AQUEOUS - UTAMI, ISNI (Jurnal Teknik Kimia, 2009)
Cathodic Protection is one of the method to Control Corrosion rate thermodynamically by applying steel as cathode. Application of this methode is by flow the DC current through electrolite to steel so that potential interface between steel and electrolite goes to immun area or until paricular value which corrosion speed allowed (minimum).Cathodic Protection using sacrificial anode methode was researched in electrochemistry way.Experiment was done to AISI SAE 1018 steel in NaCl environtment 3.5% within 168 to 840 hours using sacrificial anode Al and Zn.From analysis data using mass loss methode, Al anode able to decrease steel corrosion speed untill 82% and Zn for 50. %Keyward :Cathodic protection, sacrificial anode